Analisis Hoaks Yang Dipublikasikan Berulang - Iswara, Agus Ari (Jurnal Pekommas, 2023)
This study is about repeated hoaxes. This is qualitative research. The online library method was applied to collect references, theories, and data. Data triangulation was needed to ensure that the data used were fact-checked and verified as hoaxes. Data collected by the tapping method and note-taking technique. Data were collected from Turnbackhoax.id. The ‘Search’ menu on the Turnbackhoax.id website was used to find data with some keywords. Data were presented in the form of links of the fact-checked result of old hoaxes and recycled hoaxes followed with its clarification. Data analysis used the descriptive method assisted by the triangulation method with theories. The result of this study showed hoax producers got an advantage over internal and external factors. The internal factor, hoax maker chose topics that seem important and were presented with a persuasive or provocative narrative. The first external factor was the level of literation of the recipient of the information. Second, environmental conditions or momentum that supported the spread of repeated hoaxes. Then, the momentum that could trigger friction in society also supports the circulation of repeated hoaxes.